2012
DOI: 10.1097/ico.0b013e318221cee0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Contact Lens–Related Corneal Ulcers at a Tertiary Referral Center

Abstract: There was a significant increase in the number of cases of presumed bacterial keratitis associated with soft CL wear over the study period from 2004 to 2007 at our institution. The significant increase in CLRU noted from 1996 to 1999 to 1999 to 2002 reported previously seems to have continued between 2004 and 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 18 publications
1
36
1
1
Order By: Relevance
“…117 Compared with bacterial keratitis, fungal keratitis is frequently associated with poorer outcomes 118 and is a recurrent problem in many parts of USA with a recent increase in contact lens wearers. [119][120][121] In developing countries, ocular trauma is a major risk factor. 31,122,123 Fungal spores are able to penetrate compromised epithelium where they germinate, expressing β-glucan and α-mannan molecules on their surface.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…117 Compared with bacterial keratitis, fungal keratitis is frequently associated with poorer outcomes 118 and is a recurrent problem in many parts of USA with a recent increase in contact lens wearers. [119][120][121] In developing countries, ocular trauma is a major risk factor. 31,122,123 Fungal spores are able to penetrate compromised epithelium where they germinate, expressing β-glucan and α-mannan molecules on their surface.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…It is also the most common cause of corneal infection associated with contact lens wear (5,6). Our research has shown that clinical and laboratory isolates of P. aeruginosa can be divided into invasive or cytotoxic strains based upon how they interact with host cells (7).…”
mentioning
confidence: 99%
“…2,12,15 Nevertheless, it is of note that Pseudomonas aeruginosa is the most frequent isolated agent in contact lens-related ulcers, while gram-positive bacteria were more strongly associated with ocular surface diseases and corneal traumas. 2,16 This might be because Pseudomonas aeruginosa is a water-borne strain that can adhere to and colonize lens materials during wearing. The bacterium usually survives in contact lens storage cases due to both its ability to produce a resistant biofilm on lenses and cases, and its endurance to contact lens disinfectants.…”
Section: Discussionmentioning
confidence: 99%